INTERSECTION LEVEL OF SERVICE FOR THE CICLORUTA BICYCLE INFRASTRUCTURE IN BOGOTA, COLOMBIA - Okon, Inah Eteng (Humanities & Social Sciences Reviews, 2021)
Purpose of the study: A satisfaction audit for use of cycling mode is aimed at the promotion of non-motorized transport which is safe, comfortable, economical and energy-efficient as critical for urban sustainability. The study examined the level of satisfaction that cyclists derive from the cicloruta based on the intersections in the network. Methodology: The methodology involved the use of primary data such as 680 perceptions of satisfaction ratings; physical and operational characteristics of road infrastructure (measurement and observational) data; and shapefile of the cicloruta. The relationship between variables was examined using correlation statistics, while the ordered probit model was used to estimate the parameter, predicted logit and predicted probabilities. Main Findings: An estimated model for intersection bicycle level of service (IntBLOS) revealed that the volume of vehicular and total intersection legs are factors with a high influence on cyclist’s level of satisfaction. The model was used in ArcGIS to compute IntBLOS scores at both segment and facility levels. Since segments are not independent of intersections or vice versa, the study used these two independent models to estimate the level of bicyclist’s satisfaction. Applications of this study: This study undoubtedly takes a step towards demonstrating a non-motorised transport infrastructure audit which can help address specific concerns of cyclists and thus enhance ridership in the study area. Elsewhere, especially in the developing countries applicability of this methodology shall be with modifications on measurement and observation data that reflects peculiar local traffic situations. Novelty/Originality of this study: The findings of this paper has stimulated further conversation on the factors of cycling in the city with its ambitious cycling infrastructure. It has also provided planners with an infrastructure audit methodology to enhance cycling safely and sustainably. The study recommended proper enlightenment of motorists and cyclists alike on their right of way and most importantly, the redesign of most intersections in the study area to reflect the present cycling realities of Bogota.